Cloning and characterization of Escherichia coli K-12 regulator gene tyrR. - Cornish, E C (American Society for Microbiology (ASM), 1982)
The Escherichia coli K-12 regulator gene tyrR was cloned into the multicopy plasmid pBR322 from a lambda(Tn10)tyrR+ specialized transducing phage. Further subcloning localized the gene within a 2.1-kilobase region. Analysis of plasmid-coded proteins showed that the tyrR gene codes for a 63,000-dalton polypeptide.